2010
DOI: 10.1186/1471-2156-11-16
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of rice grain shape using a recombinant inbred line population derived from two contrasting parents and fine mapping a pleiotropic quantitative trait locus qGL7

Abstract: BackgroundThe three-dimensional shape of grain, measured as grain length, width, and thickness (GL, GW, and GT), is one of the most important components of grain appearance in rice. Determining the genetic basis of variations in grain shape could facilitate efficient improvements in grain appearance. In this study, an F7:8 recombinant inbred line population (RIL) derived from a cross between indica and japonica cultivars (Nanyangzhan and Chuan7) contrasting in grain size was used for quantitative trait locus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
123
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(136 citation statements)
references
References 27 publications
8
123
1
4
Order By: Relevance
“…It seems that our results are similar to the data from GL7. Genes regulating rice grain size or shape on chromosome 7, such as qGL7, qGL7-2, and GS7, have been mapped using several populations (Bai et al 2010;Shao et al 2010Shao et al , 2012Qiu et al 2012). These four genes are close to SLG7, but none of them have been cloned.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that our results are similar to the data from GL7. Genes regulating rice grain size or shape on chromosome 7, such as qGL7, qGL7-2, and GS7, have been mapped using several populations (Bai et al 2010;Shao et al 2010Shao et al , 2012Qiu et al 2012). These four genes are close to SLG7, but none of them have been cloned.…”
Section: Discussionmentioning
confidence: 99%
“…A great number of QTLs have been identified for rice grain size and shape by using different mapping populations (Bai et al, 2010(Bai et al, , 2012Huang et al, 2013;Lou et al, 2009). However, most mapping populations used in those studies derived from crossing between medium grain size parents (Bai et al, 2010). In this study, a large grain size parent, NYZ, and a relatively small grain size parent, Ce253, were used to generate mapping population for grain size QTL analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Among four grain length QTLs, qGL-3, flanked by markers 03M36.3 and 03M33.1, was mapped at the end of the short arm of chromosome 3 with 27.60% phenotypic contribution (Table 4). It should be mapped at the same locus as qGL3c, another QTL for grain length, which was identified in a mapping population also using NYZ as favorable grain size parent (Bai et al, 2010). It has been reported that QTL for grain size and shape traits mainly controlled by cloned loci, such as GS3, GS5, GW2, GW5, and GW8, with major effect on grain length, grain width, and/or grain weight (Fan et al, 2006(Fan et al, , 2009Mao et al, 2010;Song et al, 2007;Shomura et al, 2008;Li et al, 2011;Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Grain morphology is the inherited characters of a variety (Wan et al, 2008;Bai et al, 2010). Different morphology (Table 4) was shown in the rice cultivars although they are given a similar name by farmers.…”
Section: Grain Morphologymentioning
confidence: 99%